Process and Source of Innovation in SME: Case of Indonesia's Food and Beverage Firms - Prihadyanti, Dian (SBM ITB, 2013)
In a free trade environment, the requirements to remain competitive become more demanding. The requirements make innovation more necessary to be done, and strongly associated with the ability to take advantage on scientific achievement. Therefore, innovation process conducted becomes an important determinant for its final outcome. Nevertheless, how innovation occurs in SMEs is still rather unknown exactly. This paper attempts to analyze innovation process in SMEs especially in low-technology sectors, particularly in food and beverage sector, in terms of sources of innovation which is related with sources of information and knowledge. This study use case study approach within two food and beverage SMEs. The innovation process is seen through the decision making process approach. This study reveal several important conclusions. In food and beverage sector, it appears that the process of innovation in the SMEs do not only involve the internal but also external parties. The process of innovation was still very simple. Generally, the approach in decision making and understanding of innovation is more static, non-rational, informal and hierarchical. Nevertheless, to complement the result, further studies still need to be conducted to obtain stronger justification of conclusions and policy recommendation.Keywords: innovation process, decision making, source of innovation, food and beverage sector, SME